Determinación de las propiedades físicas, composición química y evaluación de la actividad biológica y antioxidante del aceite esencial de la especie Clinopodium taxifolium (Kunth) Govaerts de la provincia de Loja - Aldas Palacios, Ana Belén (2014)
The chemical, physical and biological and antioxidant activity of the essential oil obtained by distillation Clinopodium taxifolium by stripping with water vapor was determined. The chemical composition of the essential oil were determined by gas chromatography-mass spectrometry GC / MS and the flame ionization detector GC / FID; obtaining a total of 48 compounds representing 97,20% of the essential oil, being the main compounds: mentha (3,19%), Iso-pulegyl acetate (7,30%), α - Copaene (4,98%) , Z-Caryophyllene (24,09%), Germacrene-D (12,82%), Bicyclogermacrene (8.80%) and δ-cadinene (5.89%). Among the physical properties has the refractive index (nD20 = 1,4904) of and the relative density (0,9317 g / cm3). This species has no antibacterial activity, but has a slight activity against Trichophyton rubrum (500 μg/mL). Antioxidant activity was also assessed by two methods: ABTS+. and DPPH.. for each method DPPH. mean inhibitory concentration (IC50) was calculated. Clinopodium taxifolium showed higher antioxidant activity with the DPPH. method with an IC50 = 17.15×10-6 g/mL. Facing the ABTS+. method was that the IC50 value = 7.3×10-7 g/mL.